2020
DOI: 10.1111/jfb.14295
|View full text |Cite
|
Sign up to set email alerts
|

American eels produce and release bile acid profiles that vary across life stage

Abstract: The American eel (Anguilla rostrata) is an imperilled fish hypothesized to use conspecific cues, in part, to coordinate long‐distance migration during their multistage life history. Here, holding water and tissue from multiple American eel life stages was collected and analysed for the presence, profile and concentration of bile acids. Distinct bile acid profiles were identified in glass, elver, yellow eel and silver eel holding waters using ultraperformance liquid chromatography high‐resolution mass spectrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…A study in American eel has confirmed the active bile acid production in different life stages of the eel (Schmucker et al . 2020). Our study suggests the gut microbiota may help in such process.…”
Section: Resultsmentioning
confidence: 99%
“…A study in American eel has confirmed the active bile acid production in different life stages of the eel (Schmucker et al . 2020). Our study suggests the gut microbiota may help in such process.…”
Section: Resultsmentioning
confidence: 99%
“…However, not all BAs have a positive effect; some BAs would bring negative effects; for example, both TCA (Taurocholic acid) and bovine bile salt supplementation in a low fishmeal diet to the Atlantic salmon could cause slight or moderate inflammation of the distal intestine [20]. At present, in mammals, the profile of BAs generated a lot of results and interesting discoveries [21,22], while there were few reports that concentrated on BAs in fish, since most of them focused on the roles of BAs in fish pheromone systems and the identification of some new BAs in saltwater fish [23][24][25][26]. In general, BAs in fish have undergone fewer studies, which are relatively one-sided [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…[19]. At present, in mammals, profile of BAs has got a lot of results and interesting discoveries have been found [20,21], while there were few reports about concentrated on BAs in fish, since most of them focused on roles of BAs in fish pheromone systems and identification of some new BAs in saltwater fish [22][23][24][25]. In general, BAs in fish have less study, and which is relatively one-sided [26][27][28].Previous studies of our team suggested that high plant protein induced common carp liver injury, while BAs supplementary could help to alleviate [29], but which BA played the leading role or how to affect liver health?…”
Section: Introductionmentioning
confidence: 99%